Dydaktyka literatury a wiedza o literaturze = Literature didactics and the knowledge of literature - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper discusses the relations between literatura didactics and the literary knowledge. It has been claimed that the above disciplines have the same object of scientific investigation, while they differ in the subject of their research.
Keywords: dydaktyka literatury; literaturoznawstwo